Factores de riesgos físicos, químicos, biológicos y ergonómicos a los que están expuestos el personal auxiliar de enfermería del Hospital Vicente Rodríguez Witt de la ciudad de Loja - Guerrero Cuenca, Amada Gabriela (2015)
The present work of thesis allowed to determine the factors of occupational risks to which they are exposed Auxiliary Nursing that work at the Vicente Rodriguez Witt Hospital of the city of Loja, it was a descriptive study with a quantitative approach, involving 25 assistants Nursing, for data gathering was used as technique a survey with a previously structured questionnaire, the results are represented in simple graphics, in terms factor of physical risk, the most prevalent are radiations that affects 48% of the staff, 75% are continuously exposed to handling disinfectants considered as a chemical risk, as biological risk factor handling body fluids and handling sharps affecting 46% and ergonomic risk, 72% are exposed to activities movements require muscle strength. Ultimately occupational health focuses on the process of health and disease health workers and auxiliary of infirmary, although reports of accidents are old, in the field of occupational risks in the area Nursing is not exactly known statistical data to determine their causes to propose alternative of solutions to improve the job security of the workers and ensure service quality. The Nursing Assistant Personal faces risks of accidents or diseases noted as frequent risks contagion that they can suffer due to handling people with infectious diseases; radiation exposure by the use of equipment and dispositive that emit X-rays; and contact with chemical or biological substances. Keywords: nursing assistant, occupational, physical, chemical, biological, ergonomic risks